2016
DOI: 10.1080/23273798.2016.1209531
|View full text |Cite
|
Sign up to set email alerts
|

Processing temporal presuppositions: an event-related potential study

Abstract: The ability to efficiently process presuppositions, which contain information that the speaker believes to be in the background to the conversation, is essential for effective communication. To get a deeper understanding of the nature and the time-course of temporal presupposition processing, we examined event-related potential (ERPs) evoked by the word again in two types of sentence contexts. The word again was presented in contexts that supported a presupposition (e.g., Jake had tipped a maid at the hotel on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…An alternative interpretation of the positivity comes into mind when considering another area of pragmatic reasoning, namely the field of presupposition processing. In a recent study, Jouravlev et al () found a positivity for the processing of presupposition triggers such as again in sentences pairs like Jake had never tipped a maid at the hotel before . Today he tipped a maid at the hotel again, although the hotel paid its maids good wages when compared to pragmatically unmarked control conditions.…”
Section: Discussionmentioning
confidence: 97%
“…An alternative interpretation of the positivity comes into mind when considering another area of pragmatic reasoning, namely the field of presupposition processing. In a recent study, Jouravlev et al () found a positivity for the processing of presupposition triggers such as again in sentences pairs like Jake had never tipped a maid at the hotel before . Today he tipped a maid at the hotel again, although the hotel paid its maids good wages when compared to pragmatically unmarked control conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Brouwer et al, 2012;Burkhardt, 2006Burkhardt, , 2007Jouravlev et al, 2016;Schumacher, 2009, see also Donchin & Coles, 1988;Polich, 2007). More specifically, according to Brouwer et al (2012), late positive components reflect the "construction, revision, or updating of a mental representation of what is being communicated" (Brouwer et al, 2012, p. 137; see also Brouwer, Crocker, Venhuizen, & Hoeks, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing more demanding inferences resulted in larger P600 effects, whereas no N400 effects were observed when the context did not support the presupposition. Jouravlev et al (2016) also examined ERPs, but focused on the PSP trigger again (in English). Participants read sentences in contexts that either supported the presupposition (e.g., "Jake had tipped a maid at the hotel once before.…”
Section: Presuppositions and Their Immediate Processingmentioning
confidence: 99%
“…These effects also indicate that a presupposition trigger is considered immediately upon encountering it. However, recent studies suggest that different types of presupposition triggers differ in processing (Abrusán 2011;Domaneschi et al 2014;Domaneschi and Di Paola 2018;Jouravlev et al 2016;Tiemann et al 2015). Against this background, it is unfortunate that Tiemann et al (2011) did not analyze reading times for the different triggers separately.…”
Section: Presuppositions and Their Immediate Processingmentioning
confidence: 99%